Early Development of Infants with Turner Syndrome. Issue 6 (August 2020) - Pretzel, Rebecca Edmondson; Knickmeyer, Rebecca C.; DeRamus, Margaret; Duquette, Peter; Okoniewski, Katherine C.; Reinhartsen, Debra B.; Cornea, Emil; Gilmore, John H.; Goldman, Barbara D.; Davenport, Marsha L.; Hooper, Stephen R.
ABSTRACT: Objective: To examine the early cognitive, temperament, and adaptive functioning of infants and toddlers with Turner syndrome (TS). Methods: Cognitive abilities were measured using the Mullen Scales of Early Learning at 1 year of age for 31 girls with TS and compared with neurotypical female (N = 53) and male (N = 54) control groups. Temperament (Carey Toddler Temperament Scales) and adaptive functioning (Vineland Adaptive Behavior Scales–Second Edition) were measured at 1 year of age and compared with normative data. An exploratory analysis of cognitive/developmental trajectories was also conducted comparing age 12-month to 24-month time points for 22 TS subjects. Results: Infants with TS performed largely within the average range for adaptive behavior, temperament, and early cognitive development with some increased risk for delays in language and significant increased risk for delays in motor skills ( p < 0.001). Although exploratory, there was some suggestion of slower rates of progression in fine-motor and visual reception skills from 12 to 24 months of age. Conclusions: Infants and toddlers with TS exhibit a relatively positive neurodevelopmental profile overall, with some indication of an increasing gap in function in fine-motor and visual perceptual abilities as compared to neurotypical peers. It is unclear whether these apparent differences represent normal variability in this very young population or, perhaps, are early precursors of later phenotypic characteristics of TS in the school-age and young adult years.